Plasma VEGF Concentrations and Ketamine's Effects on Suicidal Ideation in Depression With Suicidal Ideation - Zheng, Wei; Gu, Li-Mei; Zhou, Yan-Ling; Wang, Cheng-Yu; Lan, Xiao-Feng; Zhang, Bin; Ning, Yu-Ping (Frontiers in Psychiatry, 2022)
Objectives: Accumulating evidence supports a role for vascular endothelial growth factor (VEGF) in the pathogenesis of depression, but its relationship with the antisuicidal effects of ketamine is not clear. Our objective was to determine whether there was an association between the plasma VEGF (pVEGF) concentrations and the antisuicidal response to serial ketamine infusions. Methods: Six ketamine infusions (0.5 mg/kg) over a 12-day period were administered to sixty depressed individuals suffering from suicidal ideation. The Hamilton Depression Rating Scale (HAMD) suicide item, the Montgomery-Åsberg Depression Rating Scale (MADRS) suicide item, and the Beck Scale for Suicide Ideation (SSI-part I) were used to assess suicidal ideation at baseline, one day after the first infusion (day 1), one day following the last infusion (day 13), and again two weeks post-infusion (day 26). For this purpose, plasma was obtained at baseline, day 13 and 26. Results: The rates of antisuicidal response to ketamine were 61.7% (37/60), 81.7% (49/60), and 73.3% (44/60) at days 1, 13 and 26, respectively. The linear mixed model revealed significant time effects on suicidal ideation and pVEGF concentrations over time (all Ps<0.05). Antisuicidal responders did not have significantly altered pVEGF concentrations compared with nonresponders on day 13 and day 26 (all Ps>0.05). No significant correlation was found between the baseline pVEGF concentration and suicidal ideation as measured by the SSI part 1, HAMD suicide item and MADRS suicide item on days 1, 13 and 26 (all ps>0.05). Conclusion: This preliminary finding does not support a role for VEGF in the antisuicidal effects of serial ketamine treatments in individuals with depression and suicidal ideation. Further research is needed to confirm and expand these findings.